1994
DOI: 10.1021/ma00085a037
|View full text |Cite
|
Sign up to set email alerts
|

End-Functionalized Polymers. 2. Quantification of Functionalization by Time-of-Flight Secondary Ion Mass Spectrometry

Abstract: The applicability of time-of-flight secondary ion mass spectrometry (TOF-SIMS) for quantification of functionalization is demonstrated using five 1.0 X103 g/mol polystyrene samples which were synthesized by living anionic polymerization. The polymerizations were functionally terminated to various extents (0,25,50,75, and 100%) by using sequential termination techniques with chlorodimethylphenylsilane and methanol. Two distinct molecular weight distributions of intact oligomer signals are resolved in the TOF-SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…It can be directly observed that [C 7 H 5 O] (7d) is absent in 8 but present in 9. Thus, it seems that ionic bonds (8) do not allow the formation of fragments 7d but they are observed for covalent bonds (end groups 7 and 9). Several explanations can be proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be directly observed that [C 7 H 5 O] (7d) is absent in 8 but present in 9. Thus, it seems that ionic bonds (8) do not allow the formation of fragments 7d but they are observed for covalent bonds (end groups 7 and 9). Several explanations can be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, with SIMS, it is also possible to desorb oligomers and then to obtain the molecular weight distribution similar to MALDI. 8,9 Oligomer desorption is generally restricted to masses below 10 000 (100 000 with MALDI). For this purpose, polymers have to be prepared as very thin films on a metallic substrate (most often silver).…”
mentioning
confidence: 99%
“…Secondly, we wanted to determine whether the relative peak intensities at each degree of polymerization in the mass spectra were true representations of the siloxanolate initiator populations. The earlier mass spectral studies did not establish this [13][14][15]. The third issue addressed in this study was to evaluate the changes in peak intensities as a function of reaction conditions such as the polymerization time, initiator concentration, and the reaction temperature.…”
Section: Inear Polydimethylsiloxane (Pdms) Is Primarilymentioning
confidence: 99%
“…A new approach for studying these systems was introduced by Hunt et al [13,14] where time of flight secondary ion mass spectrometry (TOF-SIMS) was used to determine the relative amounts of initiator species (Scheme 2: s-1, -2, and -3) from the sec-butyllithium initiated ring-opening polymerization of D 3 . Unlike the earlier studies that were restricted to analyzing low molecular weight oligomers, Hunt and coworkers analyzed the higher mass final polymer product.…”
Section: Inear Polydimethylsiloxane (Pdms) Is Primarilymentioning
confidence: 99%
“…All spectra contain a peak at m/z 943.30 corresponding to the dendron cationized by adventitious sodium Na C ion. 44 Here, we illustrate that this sensitivity can be used to give information about the dendron end-functionality provided that molecular or quasimolecular ions are collected.…”
Section: Cationization To Determine the Molecular Weight Of Aliphaticmentioning
confidence: 99%